The transfer of a European company's in-house abstracting service to the Philippines a case study of its growth and development - Sonido, Ernesto G. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
This case study observes the transfer of an in-house abstracting service of European company to the Philippines. It looks at the reasons behind the transfer and the developmental stages of the transfer. In particular, the study attempts to look at the issues, challenges and solutions formulated for the completion of the transfer.